2016
DOI: 10.1002/glia.23048
|View full text |Cite
|
Sign up to set email alerts
|

ST8SIA2 promotes oligodendrocyte differentiation and the integrity of myelin and axons

Abstract: ST8SIA2 is a polysialyltransferase that attaches polysialic acid to the glycoproteins NCAM1 and CADM1. Polysialylation is involved in brain development and plasticity. ST8SIA2 is a schizophrenia candidate gene, and St8sia2 −/− mice exhibit schizophrenia‐like behavior. We sought to identify new pathological consequences of ST8SIA2 deficiency. Our proteomic analysis suggested myelin impairment in St8sia2 −/− mice. Histological and immune staining together with Western blot revealed that the onset of myelination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…In addition, although to our knowledge there was no previous study detailing the impact of St8sia2 deficiency on neonatal amygdala development, several studies have revealed alterations in other brain regions occurring after birth in St8sia2−/− mice. The reported alterations include a decrease in GABA neurons in the prefrontal cortex observed at P1, but not E16.5; [81] deficits in olfactory interneurons only seen at P5; [82] and a decrease in myelination observed from P15 onwards [83]. More generally, polysialylation is an essential process involved in the migration and clustering of neural and glial precursors [23,81,84], axonal growth and fasciculation [85], synapse formation and plasticity [86,87], and myelination [83].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although to our knowledge there was no previous study detailing the impact of St8sia2 deficiency on neonatal amygdala development, several studies have revealed alterations in other brain regions occurring after birth in St8sia2−/− mice. The reported alterations include a decrease in GABA neurons in the prefrontal cortex observed at P1, but not E16.5; [81] deficits in olfactory interneurons only seen at P5; [82] and a decrease in myelination observed from P15 onwards [83]. More generally, polysialylation is an essential process involved in the migration and clustering of neural and glial precursors [23,81,84], axonal growth and fasciculation [85], synapse formation and plasticity [86,87], and myelination [83].…”
Section: Discussionmentioning
confidence: 99%
“…ST8SIA2 knock out mouse models exhibit delayed myelination and decreased myelin content, including thinner sheaths, irregularly shaped axons, and increased white matter lesions in adulthood. ST8SIA2 knockout mice also exhibit increases in the number of immature oligodendrocytes in the cortex and the corpus callosum that may imply a blockade of OPC differentiation to myelinating oligodendrocytes (Szewczyk et al, ).…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Cells with nuclear Olig2 expression were negative for GS or GFAP. Extranuclear signal in the Olig2-channel occurred in both lowDeg and highDeg samples, in the presence and absence of primary antibodies, and was mainly interpreted as unspecific secondary antibody binding (Supporting Information,Figures S4 and S5, white circles),(Rhee et al, 2009;Szewczyk et al, 2017). However, atypical cytosolic/extranuclear expression of Olig2 as a possible consequence of the disease cannot be excluded.…”
mentioning
confidence: 99%